2014
DOI: 10.1152/ajpheart.00732.2013
|View full text |Cite
|
Sign up to set email alerts
|

PKC activation increases Ca2+sensitivity of permeabilized lymphatic muscle via myosin light chain 20 phosphorylation-dependent and -independent mechanisms

Abstract: The contractile activity of muscle cells lining the walls of collecting lymphatics is responsible for generating and regulating flow within the lymphatic system. Activation of PKC signaling contributes to the regulation of smooth muscle contraction by enhancing sensitivity of the contractile apparatus to Ca(2+). It is currently unknown whether PKC signaling contributes to the regulation of lymphatic muscle contraction. We hypothesized that the activation of PKC signaling would increase the sensitivity of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 52 publications
2
28
1
Order By: Relevance
“…The increased biosynthesis of prostaglandins, and possibly Ca 2+ sensitization also resulting from these changes, culminates in increased uterine contractions. Dougherty et al (33) have recently shown that PKC activation increases Ca 2+ sensitivity of permeabilized lymphatic muscle via myosin light chain 20 phosphorylation-dependent and -independent mechanisms, and this may contribute to the sensitization in myometrium. It is also likely that actin dependent mechanisms of Ca 2+ sensitization are evoked (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The increased biosynthesis of prostaglandins, and possibly Ca 2+ sensitization also resulting from these changes, culminates in increased uterine contractions. Dougherty et al (33) have recently shown that PKC activation increases Ca 2+ sensitivity of permeabilized lymphatic muscle via myosin light chain 20 phosphorylation-dependent and -independent mechanisms, and this may contribute to the sensitization in myometrium. It is also likely that actin dependent mechanisms of Ca 2+ sensitization are evoked (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…(ii) The lymphatic muscle contractile force increases with cytosolic Ca 2+ concentration (with saturating kinetics); the maximum possible force decreases with the radius (to reproduce the known length-force relationship) (22)(23)(24)(25)(26). (iii) Ca 2+ accumulates in the cytosol at a constant, slow rate (i.e., influx through T-type channels) (23,27,28) and is depleted via ion pumps (23,29).…”
Section: Significancementioning
confidence: 99%
“…Rho Kinase (ROCK), which phosphorylates the MLC phosphatase (MLCP) targeting subunit MYPT-1, leading to inactivation of MLCP, also promotes tonic constriction of lymphatics (Hosaka et al, 2003; Kurtz et al, 2014b; Souza-Smith et al, 2013). There is also evidence that PKC increases Ca 2+ -sensitivity by activating CPI-17-mediated inhibition of MLCP to increase tone (Dougherty et al, 2008; Dougherty et al, 2014). New evidence also suggests that lymphatic tone can be sustained by slow-cycling latch bridges (Dougherty et al, 2014), as seen in vascular smooth muscle (Dillon et al, 1981).…”
Section: Impact Of Mechanical Forces On Collecting Lymphatic Contractmentioning
confidence: 99%
“…There is also evidence that PKC increases Ca 2+ -sensitivity by activating CPI-17-mediated inhibition of MLCP to increase tone (Dougherty et al, 2008; Dougherty et al, 2014). New evidence also suggests that lymphatic tone can be sustained by slow-cycling latch bridges (Dougherty et al, 2014), as seen in vascular smooth muscle (Dillon et al, 1981). …”
Section: Impact Of Mechanical Forces On Collecting Lymphatic Contractmentioning
confidence: 99%